Economic growth and sectoral level electricity consumption nexus in India: new evidence from combined cointegration and frequency domain causality approaches. Issue 11 (1st December 2022) - Shameem P, Mohammed; Villanthenkodath, Muhammed Ashiq; Chittedi, Krishna Reddy
ABSTRACT: The re-assessment of energy – economy nexus in developing economies like India is necessitated by the constant evolution of their growth path and sectoral progression. This sectoral level examination is intended to find new evidence for the dependence of economic growth on the electricity sector in India. Using annual data of per capita real GDP and sectoral level consumption of electricity from 1971 to 2019, the combined co-integration test and Frequency domain causality approaches are employed. The estimated results show the negative impact of agricultural sector electricity consumption on growth, whereas both the Industrial and service sector enhances the production. In addition, the results of the Frequency domain causality approach support the Growth hypothesis for the study period in India, as Uni-directional causality from three sectors to economic growth were found at least in a frequency of short run to medium run. The sustainability of the growth-enhancing role of electricity consumption will depend on more sector-specific energy policies and public spending on energy infrastructure development than bland subsidies.